The career decisions of professional women with dependent children: What's changed?. Issue 4 (6th June 2016) - Woolnough, Helen; Redshaw, Jane
Abstract : Purpose: The purpose of this exploratory qualitative study was to investigate anticipated and real career decisions made by two cohorts of professional women in the UK at differing stages of the lifespan. Design/methodology/approach: Career decisions made by two cohorts of professional women following the birth of their first child at different stages of the lifespan and satisfaction with these choices in retrospect were investigated. Data analysis followed a thematic approach, and comparisons between the two cohorts were made. Findings: The study revealed much similarity between the two cohorts. The decisions women make regarding whether to return to work or not and the extent to which they are satisfied with their working arrangements are constrained by similar individual and organisational factors despite the 15-20 year gap. Research limitations/implications: Although mothers in the UK now experience strengthened legislation concerning maternity benefits and entitlements and there have been advances in flexible working, progress in relation to supporting women in reconciling work and home life when they return to work is arguably limited. Originality/value: This paper offers insights into the extent to which the career decisions made by professional women following the birth of their first child and satisfaction with these choices in retrospect have changed (or not) among two cohorts of professional women (15-20 years apart). The findings stress the importance of understanding the complex issues faced by mothers in the workforce and providing appropriate organisational support.